The drama of leadership - Pitcher, Patricia C. (John Wiley & Sons, Inc., 1997)
"As a member of the board of directors of several major international financial services corporations, Patricia Pitcher was in a privileged position to observe the inner workings of the corporate world. What she witnessed was a crisis of leadership rooted in a misunderstanding of what leading is all about. Not content to simply offer an opinion - opinions come cheap - she embarked on an eight-year research project to document the reasons for the rapid collapse of a global giant. That collapse, she shows us, began with one critical succession error and was compounded by a chronic failure to understand the importance of personality in the leadership equation. One wrong person at the helm turned a dream into a nightmare." "In The Drama of Leadership, Patricia Pitcher shares her findings and, in the process, explodes a number of popular myths about leadership, including the one that leadership and vision are qualities that can be taught in management seminars. She refutes the common belief that leaders are in short supply and proves that the corporate talent pool abounds with potential leaders whose talents either go unrecognized or are tragically undervalued. And she explains why, at a time when vision, innovation, humanity, and passion are so desperately needed, so many companies cast in leadership roles people who possess none of these qualities, and who distrust anyone who does."--BOOK JACKET.